Physiotherapy Education Activities for Neck Pain Complaints In the Sanan Tempe Chips Worker Community - Rahmadani Safitri; Yuli Rakhmawati; Safun Rahmanto (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Neck pain is one of the musculoskeletal complaints that people often complain about. Unergonomic working posture is a risk factor that can cause neck pain. For tempe chips workers, unnatural working postures are carried out for long periods of time and in repetitive movements. The aim of this activity is to provide insight and preventative efforts to prevent neck pain in the Sanan tempe chips worker community. The method for carrying out activities is educational outreach regarding good working positions and ergonomics. Also provides preventive management and reduces complaints of neck pain. The results of the activity showed that after being given education, there was an increase in insight into and knowledge of the Sanan tempeh chips workers. This increases workers' awareness of the importance of adopting ergonomic working positions to prevent neck pain. Continuous preventive and curative activities still need to be carried out to reduce the incidence of neck pain in the Sanan tempeh chip worker community.